2010
DOI: 10.3892/ijmm_00000525
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of atopic march may be the ‘social’ event of cells and molecules (Review)

Abstract: Abstract. The skin, the conjunctivae, the airways and the digestive tract compose a huge vulnerable biological surface, which is exposed to the external environment. An allergen can often trigger an allergic reaction at a number of sites or result in an atopic march. However, the mechanism of atopic march remains unclear. Less attention has been paid to the connection between the primary site and the atopic site, because current knowledge is established directly against harmful factors. Allergic hypersensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This may be a systemic reaction of the body, and the mechanisms are incompletely understood. Through literature search, Luo et al proposed a model of “social events” of cells and molecules to explain the atopic march ( 90 ). Epithelial cells, such as epidermal keratinocytes and airway epithelial cells, are the first line of defense against allergen exposure and initiate the inflammatory response by releasing proinflammatory cytokines.…”
Section: Possible Mechanisms Underlying the Atopic Marchmentioning
confidence: 99%
“…This may be a systemic reaction of the body, and the mechanisms are incompletely understood. Through literature search, Luo et al proposed a model of “social events” of cells and molecules to explain the atopic march ( 90 ). Epithelial cells, such as epidermal keratinocytes and airway epithelial cells, are the first line of defense against allergen exposure and initiate the inflammatory response by releasing proinflammatory cytokines.…”
Section: Possible Mechanisms Underlying the Atopic Marchmentioning
confidence: 99%
“…The epithelial cells produce thymic stromal lymphopoietin (TSLP), a cytokine similar to IL-7, which is involved in the allergic response and is a key factor in the onset of allergic inflammation in the skin, lungs and gastrointestinal tract [15]. TSLP is considered to be a biomarker for disruptions of the epithelial integrity, and was cited as a determining and aggravating factor in a variety of allergy models, including ovalbumin (OVA)-induced asthma, atopic dermatitis and allergic diarrhea [16].…”
Section: The Gut-lung-skin Barriermentioning
confidence: 99%
“…It is supported by numerous studies that organs sharing common embryological origins may communicate with each other even if there is no anatomical association. [27][28][29][30][31][32][33][34][35][36] The primitive foregut has been shown from a growing number of literatures as the embryological origin of respiratory and gastrointestinal epithelia. 37,38 Wang et al 39 indicated the existence of the lung-intestine communication by presenting the lung's duplication of inflammatory reactions in the bowel.…”
Section: Discussionmentioning
confidence: 99%